Benzothiazole integrated into a cryptand for ESIPT-based selective chemosensor for Zn2+ ions. Issue 22 (9th May 2019) - Gupta, Mayank; Sahana, Sunanda; Sharma, Vivekanand; Bharadwaj, Parimal K.
Abstract : A novel 2(2′-hydroxyphenyl) benzothiazole-based cryptand (L ) exhibits high fluorescence intensity in the presence of Zn 2+ ions by stopping the excited state intramolecular proton transfer (ESIPT) process with a detection limit of 0.20 μM. Abstract : A novel benzothiazole-based cryptand was designed and synthesized, and it exhibited high fluorescence intensity in the presence of Zn 2+ ions based on the metal chelation inhibition of the excited state intramolecular proton transfer (ESIPT) process. The structure of the cryptand was confirmed by NMR, mass spectroscopy and X-ray crystallography. Importantly, this probe showed high selectivity over other biologically relevant metal ions and anions and a detection limit of 0.20 μM, which is acceptable within the EPA (US) limit.